Remembering the dead collective memory and commemoration in late medieval Livonia - Strenga, Gustavs 1981- (Brepols, 2023)
"Medieval memoria - commemoration of the dead - was both a form of collective memory and a social practice that was present in every sphere of life. It shaped identities and constituted groups, thus the research of commemorative practices can tell lots about medieval communities. This study reveals the importance of memoria as a form of collective memory for different groups and institutions: urban government and guilds, the Teutonic Order, bishops and cathedral chapters, and monastic communities, in late medieval Livonia (modern day Latvia and Estonia)."
Keywords: Geschichte 1400-1520; Kollektives Gedächtnis; Memoria; Livland; Kollektivt minne; Medeltiden; Hochschulschrift